Implications of COVID-19 pandemic on sustainable consumption patterns. Evidence from Iasi County, Romania - Brumă, Ioan-Sebastian; Ulman, Simona-Roxana; Tanasă, Lucian; Cautisanu, Cristina (Frontiers in Sustainable Food Systems, 2022)
Across the literature, two broad behavior strategies toward sustainable food consumption are emphasized across the literature. The first strategy is related to sustainable product choices concerning how the outcome is produced, while the second one keeps a check on sustainable dietary patterns in terms of the composition within product categories. Considering these behavior strategies, while focusing especially on purchasing sustainable organic foods and preferring curtailment behaviors, conversion to this type of intake became a relevant objective among the specialists established for attaining sustainability. Consequently, the aim of this study was to observe the main changes in sustainable consumption patterns concerning these behavior strategies during the COVID-19 pandemic (August 2020), compared to the previous period (November–December 2019), in Iasi County, Romania. This study emphasizes an image of daily consumption that has been changed, at least regarding some specific aspects, due to the pandemic in the investigated Romanian context. First, the tendency to shop more during the working days could be generally observed and completed by the fact that the consumers felt safer in open spaces, like the food markets, compared to close spaces, be they supermarkets or grocery stores. Next, other main results showed that (1) the responsibility of consumers increased with regard to the purchase and waste of fresh vegetables and meat, preferring to buy more often and throw away less during the pandemic; (2) the behavior strategy in terms of organic food seemed to be discouraged in this period; and (3) local food appeared to have increased consumers' support. In addition, the pandemic crisis was shown as a driver in the digitalization of the shopping process. Accordingly, the COVID-19 pandemic seemed to have significant effects on sustainable consumption over the short and (at least) medium run, determining some changes in consumption patterns that could support, to a considerable extent, the effort of attaining a more sustainable path. However, our findings revealed some gaps in terms of societal knowledge about sustainable consumption and, consequently, call for the necessity of educating individuals on what this concept really means and why it is important to be achieved.